Utilization of Augmented and Virtual Reality in Geoscience - HOLUŠA, Věroslav; BENEŠ, Filip; VANĚK, Michal (GeoScience Engineering, 2022)
In today's age of modern IT technologies, it is no wonder that modern visualization tools and techniques are finding their way into areas such as geological and environmental sciences. The market offers a wide range of software resources for use and especially for the creation of scenes in virtual reality. The aim of our article is to evaluate a number of tools for creating VR content and evaluate their practical applicability. In the experiments, several tools for creating virtual reality scenes were tested and these tools were compared in terms of their parameters. The conclusion of the article shows the results, while Photomodeler and RealityCapture were the most suitable software for the academic sphere. On the contrary, Bentley ContextCapture software seems the least suitable. Keywords: Augmented reality; Benchmarking; Geoscience; Virtual reality.